Deregulation of the cell cycle and related microRNA expression induced by vinyl chloride monomer in the hepatocytes of rats. (June 2021) - Pan, Weizhe; Yu, Shengnan; Jia, Jin; Hu, Junyang; Jie, Liang; Zhang, Panhong; Wang, Qian; Yan, Xiaoyan; Qiu, Yulan
Vinyl chloride (VC) is a confirmed human carcinogen associated with hepatocellular carcinoma and angiosarcoma. However, the role of microRNAs (miRNAs) in liver cell cycle changes under VC exposure remains unclear, which prevents research on the mechanism of VC-induced carcinogenesis. In this study, male rats were injected intraperitoneally with VC (0, 5, 25, and 125 mg/kg body weight) for 6, 8, and 12 weeks. Cell cycle analysis of liver cells, miRNA-222, miRNA-199a, miRNA-195, and miRNA-125b expression in the liver and serum, and target protein expression were performed at different time points. The results showed a higher percentage of hepatocytes in the G1/G0 and S phases at the end of 6 and 12 weeks of VC exposure, respectively. MiRNA-222 expression decreased initially and then increased, whereas miRNA-199a, miRNA-195, and miRNA-125b expression increased initially and then decreased, which corresponded with changes in cell cycle distribution and related target proteins expression (p27, cyclinA, cyclinD1, and CDK6). The corresponding expression levels of miRNAs in serum did not change. Dynamic changes in miR-222, miR-199a, miR-195, and miR-125b induced by VC can lead to cell cycle deregulation by affecting cell cycle-related proteins, and these miRNAs can serve as early biomarkers for malignant transformation caused by VC.